A phase III clinical trial to evaluate the safety and immunogenicity of 23-valent pneumococcal polysaccharide vaccine (PPV23) in healthy children, adults, and elderly. Issue 1 (2nd January 2019) - Huang, Lili; Wang, Ling; Li, Hong; Hu, Yuansheng; Ru, Weiping; Han, Weixiao; Shi, Gang; Ye, Qiang; Han, Zhen; Xia, Jielai; Xia, Shengli; Xu, Miao; et al.
ABSTRACT: To evaluate the safety and immunogenicity of a newly 23-valent pneumococcal polysaccharide vaccine (PPV23), a phase Ⅲ clinical trial was conducted in population aged ≥ 2 years. We conducted a randomized, double-blinded, active controlled trial, in which 1760 participants were randomly assigned in a 1:1 ratio to receive one dose of either the test vaccine or the control commercial vaccine. The surveillance period was 28 days. The 2-fold increase rate of anti-pneumococcal for 23 serotypes varied from 49.71% to 90.96% in the treatment group and from 44.52% to 88.24% in the control group. According to −10% non-inferiority margin and 95% confidence intervals of rate difference, all the 23 serotypes of the treatment group were non-inferiority to the control group. The 2-fold increase rate of anti-pneumococcal antibody were significantly higher in the treatment group for 11 serotypes including 1, 2, 3, 4, 10A, 11A, 14, 18C, 20, 22F, and 23F. Serious adverse events occurred in 2 in 879 (0.23%) participants in the treatment group and 2 in 880 (0.23%) participants in the control group, and all the adverse events were unrelated to the vaccination. The overall adverse reaction frequency showed no difference between the treatment (51.19%) and control group (47.95%), and most adverse reactions were mild or moderate in intensity. The newly PPV23 is immunologically non-inferior to the control commercial vaccine and well tolerated in healthy Chinese population aged ≥ 2 years. Trial registration : ClinicalTrial.gov identifier: NCT02451969.